DIGITAL QUALITY ASSURANCE HUB FOR COMMUNITY COLLEGES: A MODEL FOR ENHANCING QUALITY MANAGEMENT AND TEACHING EFFICIENCY - Osmin, Siti Sharmila (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2025)
In the context of digital transformation, higher education institutions are increasingly required to strengthen quality assurance (QA) systems to comply with standards such as ISO 21001, the Malaysian Qualifications Agency (MQA), and the Malaysia Board of Technologists (MBOT). However, QA documentation in many community colleges remains fragmented and manually managed, leading to inefficiencies and audit preparation challenges. This paper reports a design-and-implementation case study on the development of a Digital Quality Assurance Hub at Pasir Salak Community College using Google Sites integrated with Google Workspace tools, including Drive, Docs, Sheets, and Forms. Guided by a design-based research approach, the platform was developed to centralize QA documentation, support teaching and learning activities, and facilitate systematic evidence management. User feedback, document retrieval observations, and platform usage data indicate improved accessibility, reduced duplication of records, and more efficient coordination during internal audits. Rather than claiming causal impact, the findings suggest that low-cost cloud-based tools can support digital governance and quality management practices in community college settings. This study contributes a practical reference model for Malaysian TVET institutions seeking to align QA processes with national digitalization initiatives and ISO 21001 principles using existing institutional resources.